Implementation of the Activate injury prevention exercise programme in English schoolboy rugby union - Barden, Craig (BMJ Open Sport Exerc Med, 2021)
OBJECTIVES: The implementation of the Activate injury prevention exercise programme has not been assessed in an applied context. This study aimed to (1) describe the knowledge and perceptions of school rugby coaches and players towards injury risk, prevention and Activate and (2) evaluate Activate implementation in schoolboy rugby using the reach, effectiveness, adoption, implementation and maintenance framework. METHODS: Bespoke electronic surveys were administered to coaches (including support staff) and players at participating English schools (2018–2020). Most questions and statements were answered using a 7-point Likert scale. At baseline, participants detailed their Activate awareness and perceptions of injury risk and prevention in schoolboy rugby. At postseason, participants reported Activate use throughout the study and their perceptions towards the programme. RESULTS: At baseline, significant differences existed between coaches (n=106) and players (n=571) in Activate awareness (75% and 13% respectively; χ(2)=173.5, p<0.001). Coaches perceived rugby had a significantly greater injury risk than players, while holding more positive perceptions towards injury prevention. At postseason, coaches reported greater Activate adoption compared with players (76% and 18% respectively; χ(2)=41.8, p<0.001); 45% of players were unaware if they used the programme. Median session adherence was twice weekly, with a median duration of 10–15 min. This suggests Activate was not implemented as intended, with recommendations of three 20 min sessions per week. Both groups identified common barriers to implementation, such as lack of time and inclusion of a ball. CONCLUSION: Coaches are instrumental in the decision to implement Activate. Targeting behavioural change in these individuals is likely to have the greatest impact on intervention uptake.